Relações entre inteligência, criatividade e funções executivas: um estudo multicasos - Porto, Silvia Beltrame (Brasil, 2018)
Intelligence can be defined as a set of cognitive abilities emerging from different intellectual processes, builded in exclusive paths of development, as a result of the interaction biological and cultural factors. The intelligence quotient (IQ), known as the expression of an individual's level of ability in relation to their normative data, lines up groups at intelligence curve of development, describind groups of intellectual disability and giftedness. However, it is argued in this study, that such groups do not opose each other in completude, wich means that intelectual disabilities and giftedness are configured by points of strength and fragility. On the other hand, the relationship between intelligence, executive functions and creativity have provoked fruitful debates. In this sense, the current study aims to investigate how these dimensions can relate with the extremity groups of intelligence curve, investigate the relationships between these dimensions in the two extremes of the intelligence curve, triyng to understand these neuropsychological profiles beyond a quantitative approach. Sixteen individuals between 12 and 20 years old, with IQ classifications at the two extremes of the intelligence curve, participated in this study. The dimensions of intelligence, creativity and executive functioning were evaluated. Data were analyzed through descriptive statistics and cluster analysis. The main results suggests that verbal comprehension dimension of intelligence is the domain wich better explains the difference between groups, and processing speed is the one with smaller diferences between them. In terms of executive functioning, operational memory and cognitive flexibility emerged as the most distinct abilities between groups. At last, enrichment factor of ideas explained the main diferences between individuals of both groups, related to criativity production. It is hoped that the results found may subsidize interventions in both groups, either considered with special educational needs, from the profiles that characterize them, considering fragility points, but especially the points of strength, moving towards an understanding of special education beyond the limits imposed by the quotient of intelligence, since it is not here considered as destiny.
Keywords: Deficiência intelectual; Altas habilidades/superdotação; Funções executivas; Criatividade; CNPQ::CIENCIAS HUMANAS::PSICOLOGIA